Serological Levels of Anti-clathrin Antibodies Are Decreased in Patients With Pseudoexfoliation Glaucoma - Beutgen, Vanessa M.; Pfeiffer, Norbert; Grus, Franz H. (Frontiers in Immunology, 2021)
Evidence for immunologic contribution to glaucoma pathophysiology is steadily increasing in ophthalmic research. Particularly, an altered abundance of circulating autoantibodies to ocular antigens is frequently observed. Here, we report an analysis of autoantibody abundancies to selected antigens in sera of open-angle glaucoma patients, subdivided into normal-tension glaucoma (N=31), primary open-angle glaucoma (N=43) and pseudoexfoliation glaucoma (N=45), versus a non-glaucomatous control group (N=46). Serum samples were analysed by protein microarray, including 38 antigens. Differences in antibody levels were assessed by ANOVA. Five serological antibodies showed significantly altered levels among the four groups (P<0.05), which can be used to cluster the subjects in groups consisting mainly of PEXG or POAG/NTG samples. Among the altered autoantibodies, anti-Clathrin antibodies were identified as most important subgroup predictors, enhancing prospective glaucoma subtype prediction. As a second aim, we wanted to gain further insights into the characteristics of previously identified glaucoma-related antigens and their role in glaucoma pathogenesis. To this end, we used the bioinformatics toolset of Metascape to construct protein-protein interaction networks and GO enrichment analysis. Glaucoma-related antigens were significantly enriched in 13 biological processes, including mRNA metabolism, protein folding, blood coagulation and apoptosis, proposing a link of glaucoma-associated pathways to changes in the autoantibody repertoire. In conclusion, our study provides new aspects of the involvement of natural autoimmunity in glaucoma pathomechanisms and promotes advanced opportunities towards new diagnostic approaches.